Writing Cartography's Enlightenment. (1st October 2020) - Edney, Matthew H.; Pedley, Mary S.
ABSTRACT: The Enlightenment poses a particular problem for map history. The period acquired a special significance as the historical fulcrum in the narrative of the history of cartography. This essay provides an historiographical summary of how the Enlightenment was accorded this significance, how it was called into question with the development of sociocultural approaches to maps and mapping, and how a comprehensive history of mapping in the period 1650–1800 – undertaken as Volume Four of the multi-volume series The History of Cartography – requires a completely restructured approach to map history.